Risk assessment and the setting of priorities in occupational health and safety. - Rantanen, Jorma (Scandinavian Journal of Work, Environment & Health, 1981)
Risk management is a concept central to present-day occupational health and safety. Decisions concerning the regulations of risks are based on the results of risk assessment. To date, no systematic approach to the assessment and management of risk has been developed. The issue is a difficult one because it involves combining scientific analyses with societal and political decision making. It is crucial that that risk assessor and risk manager identify the model according to which risk is regulated in his particular society. This review presents the consecutive steps used to assess risks. Also described is the linking of the assessed risks to the setting of priorities in decisions of risk management.
Keywords: occupational health and safety; priority; risk acceptance; risk assessment; risk estimation; risk evaluation; risk identification; risk management; risk regulation